Production and Recovery of Succinic Acid from Oil Palm Frond (OPF) Fermentation - Ramli, Nazatul Aziqah; Markom, Masturah; Luthfi, Abdullah Amru Indera (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
This study aimed to determine the production of succinic acid by using different nitrogen sources in oil palm frond (OPF) fermentation and the recovery of succinic acid. A comparison between two nitrogen sources, i.e., yeast extract and peptone, was performed and a fermentation solution containing the highest concentration of succinic acid was used to carry out the recovery process. Activated carbon treatment at 4% to 6% (w/w) was performed to determine the best dosage that could be used for the recovery of succinic acid in the fermentation solution. Based on the results obtained, it was found that yeast extract was able to produce a higher concentration of succinic acid at 2.62 g/L with a yield of 1.53 g/g, compared to peptone which afforded a concentration of 1.89 g/L with a yield of 1.10 g/g. It was also found that the dose of 5% (w/w) activated carbon was the best to increase the concentration of succinic acid and adsorb other organic acids. After the activated carbon was fed into the fermentation solution, it was found that the succinic acid content increased from 2.62 g/L to 3.43 g/L with a percentage increase of 24.7%.